Extrusion fabrication process for the 3D printing of sustainable concrete structures - Cheng, Jeremiah Zhi Sheng (2018)
The research and development of 3D printing have increased exponentially over the recent years. From it being a novelty, used in design prototype to it being used in ambitious tasks like the large-scale construction of buildings and even in the biomedical industry. 3D printing technology is now getting cheaper, more accurate and faster. This project would be on the extrusion process for the 3D printing of sustainable concrete. More specifically on how the rheological properties mainly yield stress and viscosity changes under different compositions of cement. The compositions are primarily made from Portland cement, water, fly ash, sand and silica fume. The importance of understanding the rheology of cement is to ensure that the material can be delivered effortlessly through the pipes (and the pump) of the 3D printer and that the cement that is extruded from the 3D printer’s nozzle would be deposited firmly (retaining the intended shape). Hence, in this report, experiments would be carried out by measuring the rheological properties of the cement using a large-gap rheometer with the aid of various mathematical models like the Bingham, Herschel-Bulkley, modified Bingham and Casson model. This is followed by using a statistical method called ANOVA (Analysis of Variance) to find the exact relationship between the compositions and the rheological properties. With the relationship established, prediction of the rheological properties of cement can be established without the need for time-consuming experiments.